Analysis of Motor Vehicle Insurance Coverage Under Indonesian Insurance Law - Gregorius Febrian Wijaya; Gunardi Lie; Moody Rizqy Syailendra Putra (CV. Rayyan Dwi Bharata, 2023)
Motorized vehicles are one of the forms of transportation that are needed by Indonesian people to carry out their daily activities. The development of motorized vehicles in circulation will also make traffic conditions more congested. Motor vehicle insurance is insurance for losses in which there is no specific regulation in the Commercial Code (KUHD). All general general insurance provisions in the Criminal Code apply to motor vehicle insurance. The research method used is descriptive qualitative research with an empirical juridical approach. Insurance law is an object of civil law, if it is concluded that unless specified in the Commercial Law Code (KUHD) as a special provision as an agreement. An insurance agreement is an agreement in which one party (guarantor) agrees to bear the risk of an event where the event cannot be determined. On this basis the other party (the insured) is threatened and has an agreed interest in the occurrence of the insured event. The insurer will pay the insured in the form of money or other benefits that have financial value. Insurance in the Criminal Code shows that there is a scope arrangement that focuses on fire insurance, while there are various other types of insurance that also require regulation. From what has been discussed above, it can be concluded that the insurance business as an institution that collects funds belonging to the public runs its business adhering to sound business principles and is responsible for the arrangements ordered by the government and also accountability is carried out by issuing insurance policies that have been agreed upon jointly by the insured and the insurer as well as the premium payment by the insured to the insurer so that there is a transfer of risks arising between the rights and obligations between the two.